2016
DOI: 10.1589/jpts.28.1795
|View full text |Cite
|
Sign up to set email alerts
|

Self-selected intensity, ratings of perceived exertion, and affective responses in sedentary male subjects during resistance training

Abstract: [Purpose] This study examined the exercise intensity and psychophysiological responses to a self-selected resistance training session in sedentary male subjects. [Subjects and Methods] Twelve sedentary male subjects (35.8 ± 5.8 years; 25.5 ± 2.6 kg·m2) underwent four sessions at 48-h intervals: familiarization; two sessions of one repetition maximum test and a resistance training session in which they were told to self-select a load to complete 3 sets of 10 repetitions of chest press, leg press, seated rows, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“… 39 Other studies observed similar affective responses to RT in elderly sedentary women, trained young women, and sedentary men. 18 , 40 , 41 The initial intensity selected to start an RT program may be very important to training adherence, especially in elderly people with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Other studies observed similar affective responses to RT in elderly sedentary women, trained young women, and sedentary men. 18 , 40 , 41 The initial intensity selected to start an RT program may be very important to training adherence, especially in elderly people with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study that analyzed the acute responses of pleasure and RPE in two different methods (traditional vs. cluster-set). In addition, there are still few studies that analyzed the pleasure responses in the RT and most of them investigated the effect of the intensity of the training on this variable (Benites, Alves, Ferreira, Follador, & da Silva, 2016;Elsangedy, Krinski, da Silva Machado, Okano, & da Silva, 2016;Portugal et al, 2015). However, the configuration of different trainings, due to the manipulation of other acute training variables, besides the intensity, might modify the psychophysiological responses during the resistance training, more specifically, the rest interval.…”
Section: Discussionmentioning
confidence: 99%
“…injury) [70], each of which can impact exercise adherence. Such studies have typically included athletes [41,42,[70][71][72][73], otherwise healthy active or inactive adults [74][75][76][77][78][79][80] and adolescents/children [81][82][83][84], rather than focussing on clinical populations such as T2D.…”
Section: Use Of Affect To Understand and Promote Exercise Adherencementioning
confidence: 99%
“…Numerous studies have examined exercise participants' ability to self-regulate exercise intensity using measures of affect. When based on their affective response, both inactive and active healthy males and females, select an intensity of approximately 55% 1RM for resistance exercise and slightly above ventilatory threshold/50% VO2 max for aerobic exercise, which is equivalent to or above the suggested intensity to provide health and fitness benefits [74,76,77,80,83,91]. Allowing participants to choose the intensity at which they exercise based on their affective response results in increased perceived autonomy and control [74,92].…”
Section: Using Affect To Self-regulate Exercise Intensitymentioning
confidence: 99%
See 1 more Smart Citation